Penerapan Metode Reorder Point pada Persediaan Stok Barang Berbasis Website - M. Rezky Sahputra; Eka Rahayu; Nurjamiyah Nurjamiyah (Universitas Harapan Medan, 2022)
The data collection of incoming and outgoing goods is still semi-manual by being recorded in a book, then every month it is transferred to excel, making data collection not recorded accurately, so that there is often a discrepancy between the data of the goods that come out and the written data, this results in the unknown number of remaining goods being delivered. available in the warehouse for sure. That way the company does not know when to reorder its stock of goods. The purpose of this research is to build a website-based inventory information system for distribution outlet businesses or commonly called distributions. In determining the right amount of inventory to place an order for stock of goods back by using the Reorder Point method. This website was built using the PHP programming language and MySQL database as well as the CodeIgniter framework. The system development uses the Waterfall method, and the system design uses the Unified Modeling Language (UML). The results of this study are a website-based inventory information system application using the reorder point method which can be used to facilitate the process of collecting data on receipt of goods and expenditure of goods, and the reorder point method can be used as a solution in determining the inventory of an item to be reordered so as to minimize the occurrence shortage or even out of goods.